Susceptibility-weighted magnetic resonance imaging of cerebrovascular sequelae after radiotherapy for pediatric brain tumors. Issue 2 (May 2018) - Neu, Marie A.; Tanyildizi, Yasemin; Wingerter, Arthur; Henninger, Nicole; El Malki, Khalifa; Alt, Francesca; Doerr, Barbara; Schmidberger, Heinz; Stockinger, Marcus; Wagner, Wolfgang; Keweloh, Stefanie; Brockmann, Marc A.; et al.
Abstract: Background and purpose: Due to sensitive neuroimaging techniques, cerebrovascular complications such as cerebral microbleeds (CMB) and cerebral cavernous malformations (CCM) are increasingly recognized as considerable late effects after treatment for pediatric brain tumor. The aim of this study was to analyze CMB in a cohort of patients after cranial irradiation therapy for medulloblastoma or other pediatric brain tumors using susceptibility-weighted magnetic resonance imaging (SWI). Materials and methods: Forty former pediatric brain tumor patients were enrolled in this prospective cross-sectional study and examined by cranial MRI including SWI sequences. Cerebral microbleeds, clinical symptoms and disability were evaluated. Results: Thirty-six (90%) of the examined individuals (mean follow-up age 22.2 y; mean follow-up time 13.5 y) were affected by CMB. Longer follow-up time and higher craniospinal irradiation doses correlated with higher total lesion count ( p < 0.01). Thirteen patients (32.5%) presented with clinical symptoms. Individuals with CMB were more severely disabled than patients without CMB ( p < 0.05). Conclusions: Cerebrovascular sequelae occur frequently after treatment for pediatric brain tumor. In this study, a remarkable part of pediatric brain tumor patients presents with CMB. As a sign of vascular damage, they can cause clinical symptoms and may correspond to neurocognitive decline. Further studies are needed to standardize MRI protocols and to improve quality of long-term follow-up.